Hybrid MDM-PDM Based Ro-FSO System for Broadband Services by Incorporating Donut Modes Under Diverse Weather Conditions - Chaudhary, Sushank; Wuttisittikulkij, Lunchakorn; Nebhen, Jamel; Tang, Xuan; Saadi, Muhammad; Al Otaibi, Sattam; Althobaiti, Ahmed; Sharma, Abhishek; Choudhary, Sunita (Frontiers in Physics, 2021)
The ongoing demand of high-speed data has surged the wireless operators to foster new technologies for providing broadband services in sensitive locations. One of the thrust areas is hospital infrastructure where there is a need to transmit crucial bio-sensor data from the patient room to the doctor’s chamber. However, in such sensitive locations, the use of radio waves is not permitted due to its interference with other portions of electromagnetic spectrum. Moreover, radio waves can compromise the health of patients by interfering with highly sensitive medical equipment. Radio over Free Space Optics (Ro-FSO) may fulfill the demand of high-speed broadband services in such sensitive locations where radio waves are not permitted. Ro-FSO allows transmission of high-speed broadband services without the interference of other portions of electromagnetic spectrum and hence it can be an excellent solution for hospital infrastructures. However, the Ro-FSO performance is highly influenced by different adverse weather conditions, particularly haze and rainfall, which further cause attenuation in the transmission path of Ro-FSO systems. These atmospheric turbulences mainly affect the transmission link range of Ro-FSO systems. In this work, we have designed Ro-FSO system by incorporating hybrid mode division multiplexing (MDM) and polarization division multiplexing (PDM) schemes to deliver four independent channels, each carrying 10Gbps data upconverted to 40GHz radio signal, over 3.4km free space optical link operating under clear weather conditions. In addition to this, the proposed Ro-FSO link is subjected to different weather conditions, particularly partially hazy/rainy and dense fog/very rainy. The reported results indicate the achievement of acceptable bit error rate (BER≈10-3) for all channels up to 3400m FSO link under clear weather conditions, 1000m under partially haze/rain and 620m under dense fog/heavy rain.